DISPARIATAS EKONOMI ANTAR KECAMATAN DI KABUPATEN BANGKALAN - Fuad Hasan; Ikhsanudin Ikhsanudin (University of Jember, 2008)
The objective of this research were to measure and to analyze the disparity of economic growth, to identify the pattern and structure of economic growth, and to know the dependency of economic growth in Bangkalan Regency. This research used time series data during 2001-2006. The data was taken from Central Biroue of Statistic (BPS). Analysis method used to 1) indeks of regional inequality) Indeks Williamson dan Indeks Entropi Theil 2) Analysis of Regional typical 3) Analysis of scalogram dan 4) Analysis of Gravitasy. The result of research show that regional disparity of Bangkalan Regency are 0,00309 (small- williamson index) and 0,0388 (entropy index). Analysis of regional typical show that 1) Bangkalan, Kamal, Arosbaya, and Labang are clasified going forward and growth fastly ; 2) Socah, Modung, Burneh, Sepulu, and Tanjung Bumi are clasified developing fastly; 3) Kwanyar and Klampis are clasified going foward depressedly; and 4) Tragah, Blega, Konang, Galis, Tanah Merah, Geger, and Kokop are clasified. Analysis of scalogram show that 1) Tanjung Bumi, Burneh, and Socah had supproting fasility and economic growth above average growth rate; 2) Bangkalan, Kamal, Arosbaya, Labang, Modung, and Sepulu had supporting facility above average and average of economic growth rate; 3) Tragah, Blega, Kwanyar, Klampis, Konang, Galis, and Tanah Merah had less supporting facility and under average of economic growth rate; and 4) Kokop and Geger had less economic growt rate with averag Analysis of supporting facility. Gravitasi show that Bangkalan became center pint for other sub district. Key words : Disparity of economic growth, Pattern and structure economic growth